Formation and structure of ionic (Na, Zn) sulfophosphate glasses - Da, Ning; Grassmé, Oliver; Nielsen, Karsten Hansgaard; Peters, Gerhard; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2011)
Supercooled ortho- and pyrophosphate melts of the type P2O5-EO-A2O (E = Zn2+, Ca2+, Sr2+, Ba2+, Mg2+, Mn2+; A = Li+, Na+, K+) exhibit unusually high sulfate solubility. This enables facile fabrication of low-melting sulfophosphate glasses with SO3 content of up to 25 mol.%. Sulfur is incorporated into those glasses practically exclusively in the form of isolated SO42- groups. The Q-group distribution of phosphate species is dominated by Q1 and Q0 groups, whereby replacing P2O5 with SO3 results in increasing depolymerization. In this way, the glass forming region can readily be extended to compounds with an average number of bridging oxygen per phosphate anion of less than 0.5. In ionic (Na, Zn) sulfophosphate glasses, cations Zn2+ and Na2+ appear to cluster distinctively around PO43- and SO42- groups, respectively.
EAM Import::2019-03-14